Best Fit Void Filling Segmentation Based Algorithm in Optical Burst Switching Networks - Rauniyar, A. K.; Mandloi, A. S. (Journal of Advanced College of Engineering and Management, 2016)
Optical Burst Switching (OBS) is considered to be a promising paradigm for bearing IP traffic in Wavelength Division Multiplexing (WDM) optical networks. Scheduling of data burst in data channels in an optimal way is one of a key problem in Optical Burst Switched networks. The main concerns in this paper is to schedule the incoming bursts in proper data channel such that more burst can be scheduled so burst loss will be less. There are different algorithms exists to schedule data burst on data channels. Non-preemptive Delay-First Minimum Overlap Channel with Void Filling (NP-DFMOC-VF) and Non-preemptive Segment-First Minimum Overlap Channel with Void Filling (NP-SFMOC-VF) are best among other existing segmentation based void filling algorithms. Though it gives less burst loss but not existing the channel utilization efficiently. In this paper we propose a new approach, which will give less burst loss and also utilize existing channels in efficient way. Also analyze the performance of this proposed scheduling algorithm and compare it with the existing void filling algorithms. It is shown that the proposed algorithm gives some better performances compared to the existing algorithms. Journal of Advanced College of Engineering and Management, Vol.1, 2015, pp. 1-10